Cost-effectiveness of hyperthermic intraperitoneal chemotherapy at primary cytoreduction of epithelial ovarian cancer based on residual disease status - Courtney A. Penn; Erica V. Carballo; Christine S. Walsh; Oliver Zivanovic; Kenneth H. Kim (Elsevier, 2022)
Hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin when used at the time of interval cytoreductive surgery (ICS) after neoadjuvant chemotherapy (NACT) has been shown to provide a survival advantage compared to interval cytoreduction alone for patients with advanced epithelial ovarian cancer in a cost-effective manner. A recent large multi-center retrospective cohort study showed a survival advantage with HIPEC given during primary debulking surgery compared to surgery alone. While there is an ongoing randomized controlled trial examining HIPEC at the time of primary cytoreductive surgery (PCS) before chemotherapy (OVHIPEC-2), there is currently no study of this practice in the United States or cost data to inform incorporation of this practice. To help guide the use of HIPEC in the upfront setting until the results of the OVHIPEC-2 are available in 2026, a decision-analytic cost-effectiveness model of the US healthcare sector was developed for patients undergoing PCS with or without HIPEC. Effectiveness inputs were extracted from a Chinese retrospective cohort study of 425 patients who underwent PCS with HIPEC and 159 patients who underwent PCS alone. We found incremental cost effectiveness ratios (ICER) of $9,789 per life year saved (LYS) for optimal PCS, $18,164/LYS for suboptimal PCS, and $7,854/LYS for all patients. Our findings provide preliminary data to support that HIPEC at the time of primary cytoreductive surgery can be considered cost-effective regardless of residual disease status when using a standard willingness to pay threshold.